A pseudo three-dimensional electrochemical-thermal model of a cylindrical LiFePO4/graphite battery. (25th January 2019) - Chiew, J.; Chin, C.S.; Toh, W.D.; Gao, Z.; Jia, J.; Zhang, CZ.
Highlights: Pseudo 2D electrochemical coupled with 3D lumped thermal model for cylindrical LiFePO4 battery. Comprehensive list of parameters for commercially available LFP battery. Curve fitted temperature profiles during the discharge process over range of temperatures and discharge rates. Cell performs differently at lower ambient temperature and discharge rate at milder exothermic reactions. Infrared thermal images display the temperature distribution and gradient of the battery cell. Abstract: This paper introduces a pseudo three-dimensional electrochemical-thermal coupled battery model for a cylindrical Lithium Iron Phosphate battery. The model comprises a pseudo two-dimensional electrochemical cell model coupled with three-dimensional lumped thermal model. The cell is disassembled to obtain the physical dimensions of the cell components. The thermal characteristics of the cell are studied during the discharge process over a range of temperatures and discharge rates. The validity of the numerical model is demonstrated experimentally via a 26, 650 cylindrical Lithium Iron Phosphate/graphite battery cylindrical cell. Instead of infrared thermal images, series of regression models are utilized to quantify the thermal behavior at various depth of discharge under various discharge rates. The results demonstrated that the battery cell performs differently at a lower ambient temperature and lower discharge rate where the exothermic reactions are milder.